The OER Quality Standards - Beutner, Marc; Schneider, J (OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of EU-StORe project)

Insights in the OER Rating – Database – Structures, Advantages and Challanges - Beutner, Marc; Duse, C; Pechuel, R; Schneider, J (OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of EU-StORe project)

Use and Implementation of OERs in Germany - Beutner, Marc; Schneider, J (OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of EU-StORe project)

Evaluation Results concerning OER and the EU-StORe Project - Beutner, Marc; Schneider, J (OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of EU-StORe project)

OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of EU-StORe project

Innovative Ansätze zum Serious Mobile Learning für Aus- und Weiterbildung

Sounds and Audios in E-learning scenarios. Results and Discussions on the basis of the SEEL project

Innovatives Micro-Learning im Handwerk – Konzeption auf Basis der Struktur der OPALESCE Learning Units sowie handwerksbezogene Umsetzungsbeispiele aus dem Bereich Rechnungswesen - Beutner, Marc

SEEL – Expertenhandbuch. SEEL – Handbook for experts - Beutner, Marc; Schneider, J

Optical Transitions between Confined and Unconfined States in p-Type Asymmetric GaAs/InGaAs/AlGaAs QW Structures - Sitarek, P.; Ryczko, K.; Misiewicz, J.; Reuter, Dirk; Wieck, A. (Acta Physica Polonica A)

Exciton Exchange between Nearly-Free and Acceptor-Bound States of a Positive Trion Assisted by Cyclotron Excitation - Jadczak, J.; Bryja, L.; Wójs, A.; Bartsch, G.; Yakovlev, D.R.; Bayer, M.; Plochocka, P.; Potemski, M.; Reuter, Dirk; Wieck, A. (Acta Physica Polonica A)

Mensch und Computer 2016 - Usability Professionals. Tagungsband

SOFSEM 2016: Theory and Practice of Computer Science

Theory and Practice of Model Transformations - 9th International Conference ICMT 2016, Held as Part of STAF 2016, Vienna, Austria, July 4-5, 2016, Proceedings

SOFSEM 2016: Theory and Practice of Computer Science - Proceedings Volume II

Erkunden mathematischer Strukturen anstatt Interpretation in Modellen – Ein innermathematischer Zugang zu negativen Zahlen - Schumacher, Jan (Beiträge zum Mathematikunterricht 2016)

Automated Quality Analysis of Software Engineering Method Models - Fazal-Baqaie, Masud; Kluthe, Frank (Proceedings of the 4th International Conference on Model-Driven Engineering and Software Development)

Ganzheitliches Qualitätsmanagement in agilen Groß- Projekten - Fazal-Baqaie, Masud; Güldali, Baris; Grieger, Marvin (Proceedings of Projektmanagement und Vorgehensmodelle 2016)

Concept-Based Engineering of Situation-Specific Migration Methods - Grieger, Marvin; Fazal-Baqaie, Masud; Engels, Gregor; Klenke, Markus (Proceedings of the 15th International Conference on Software Reuse (ICSR))

Projekt KUBAS: Koordination ungebundener Vor-Ort-Helfer - Rauchecker, Gerhard; Schryen, Guido (Im Einsatz)

Reflections on Context in Service Research. - Voss, Chris; Perks, Helen; Sousa, Rui; Witell, Lars; Wünderlich, Nancy (Journal of Service Management)
Purpose – The purpose of this paper is to examine the nature of context and its implications for theory and research in service. Design/methodology/approach – This is a conceptual paper based on exploring existing research and theory related to context in service research. Findings – The characteristics of service make context both important and challenging, there is great contextual diversity in service research as reflected, for example in ecosystems made up of multiple contextual variables. There is a need to identify the context-specific nature of middle range theory and the contextual logic of general theory. The authors explore the challenges of context for service theory and how we might learn from theory in a particular context and test or adapt it in other contexts. Originality/value – The findings of this paper are of value to researchers seeking to develop and justify theory in service research (general, middle range or theory in use).
Keywords: Research; Service theory

Call graph construction for Java libraries - Reif, Michael; Eichberg, Michael; Hermann, Ben; Lerch, Johannes; Mezini, Mira (Proceedings of the 2016 24th ACM SIGSOFT International Symposium on Foundations of Software Engineering - FSE 2016)

Multi-device UI Development for Task-Continuous Cross-Channel Web Applications - Yigitbas, Enes; Kern, Thomas; Urban, Patrick; Sauer, Stefan (Current Trends in Web Engineering - ICWE 2016 International Workshops, DUI, TELERISE, SoWeMine, and Liquid Web, Lugano, Switzerland, June 6-9, 2016, Revised Selected Papers)

Engineering Context-Adaptive UIs for Task-Continuous Cross-Channel Applications - Yigitbas, Enes; Sauer, Stefan (Human-Centered and Error-Resilient Systems Development - IFIP WG 13.2/13.5 Joint Working Conference 6th International Conference on Human-Centered Software Engineering, HCSE 2016, and 8th International Conference on Human Error, Safety, and System Development, HESSD 2016 Stockholm, Sweden, August 29-31, 2016, Proceedings)

Customized UI Development Through Context-Sensitive GUI Patterns - Yigitbas, Enes; Sauer, Stefan (Mensch und Computer 2016 - Workshopband, Aachen, Germany, September 4-7, 2016)

Towards a Task Driven Approach Enabling Continuous User Requirements Engineering - Fischer, Holger Gerhard; Rose, Mirko; Yigitbas, Enes; Forbrig, Peter (Joint Proceedings of REFSQ-2016 Workshops, Doctoral Symposium, Research Method Track, and Poster Track co-located with the 22nd International Conference on Requirements Engineering: Foundation for Software Quality {(REFSQ} 2016), Gothenburg, Sweden, March 14, 2016.)

Towards a Model-Driven Method for Reusing Test Cases in Software Migration Projects - Jovanovikj, Ivan; Grieger, Marvin; Yigitbas, Enes (Softwaretechnik-Trends, Proceedings of the 18th Workshop Software-Reengineering & Evolution (WSRE) & 7th Workshop Design for Future (DFF))

The Impact of Communication Patterns on Distributed Self-Adjusting Binary Search Tree - Strothmann, Thim Frederik (Journal of Graph Algorithms and Applications)
This paper introduces the problem of communication pattern adaption for a distributed self-adjusting binary search tree. We propose a simple local algorithm that is closely related to the over thirty-year-old idea of splay trees and evaluate its adaption performance in the distributed scenario if different communication patterns are provided. To do so, the process of self-adjustment is modeled similarly to a basic network creation game in which the nodes want to communicate with only a certain subset of all nodes. We show that, in general, the game (i.e., the process of local adjustments) does not converge, and that convergence is related to certain structures of the communication interests, which we call conflicts. We classify conflicts and show that for two communication scenarios in which convergence is guaranteed, the self-adjusting tree performs well. Furthermore, we investigate the different classes of conflicts separately and show that, for a certain class of conflicts, the performance of the tree network is asymptotically as good as the performance for converging instances. However, for the other conflict classes, a distributed self-adjusting binary search tree adapts poorly.

"Cheap Talk with Multiple Strategically Interacting Audiences: An Experimental Study" - Li, Xinyu; Peeters, Ronald ("Cheap Talk with Multiple Strategically Interacting Audiences: An Experimental Study")

FPGA-based acceleration of high density myoelectric signal processing - Boschmann, Alexander; Agne, Andreas; Witschen, Linus; Thombansen, Georg; Kraus, Florian; Platzner, Marco (2015 International Conference on ReConFigurable Computing and FPGAs (ReConFig))

Cross-Device Integration of Android Apps - Wolters, Dennis; Kirchhoff, Jonas; Gerth, Christian; Engels, Gregor (Service-Oriented Computing)
Integrating apps on mobile devices into applications running on other devices is usually difficult. For instance, using a messenger on a smartphone to share a text written on a desktop computer often ends up in a cumbersome solution to transfer the text, because many applications are not designed for such scenarios. In this paper, we present an approach enabling the integration of apps running on Android devices into applications running on other devices and even other platforms. This is achieved by specifying adapters for Android apps, which map their services to a platform-independent service interface. For this purpose, we have developed a domain-specific language to ease the specification of such mappings. Our approach is applicable without the need to modify the existing Android apps providing the service. We analyzed its feasibility by implementing our approach and by specifying mappings for several popular Android apps, e.g., phone book, camera, and file explorer.
Keywords: Cross-Device; Integration; Android; Adapter; DSL

Überlegungen zur Inklusion an Berufskollegs - Widerspruch, Anspruch und Herausforderung - Kremer, H.-Hugo (Inklusion als Chance und Gewinn für eine differenzierte Berufsbildung)

EDITORIAL zur Ausgabe 30: Inklusion in der beruflichen Bildung - Kremer, H.-Hugo; Büchter, K.; Buchmann, U. (bwp@ Berufs- und Wirtschaftspädagogik - online)

Multiprofessionelle Teamarbeit oder multiprofessionelle Akteure: Studie zur inklusiven Bildungsgangarbeit in der Ausbildungsvorbereitung - Kremer, H.-Hugo; Kückmann, Marie-Ann (bwp@ Berufs- und Wirtschaftspädagogik - online)

UUX Method Selection - Fischer, Holger Gerhard; Kauer-Franz, Michaela; Winter, Dominique; Latt, Stefan (i-com)

Human-Centered Software Engineering as a Chance to Ensure Software Quality Within the Digitization of Human Workflows - Fischer, Holger Gerhard; Senft, Björn (Human-Centered and Error-Resilient Systems Development)

Towards a Task Driven Approach Enabling Continuous User Requirements Engineering - Fischer, Holger Gerhard; Rose, Mirko; Yigitbas, Enes (Joint Proceedings of the REFSQ 2016 Co-Located Events. 2nd Workshop on Continuous Requirements Engineering (CRE))

Mensch und Computer 2016 - Usability Professionals. Tagungsband

From Radio Telemetry to Ultra-Low-Power Sensor Networks: Tracking Bats in the Wild - Dressler, Falko; Ripperger, Simon; Hierold, Martin; Nowak, Thorsten; Eibel, Christopher; Cassens, Björn; Mayer, Frieder; Meyer-Wegener, Klaus; Koelpin, Alexander (IEEE Communications Magazine)
Sensor networks have successfully been used for wildlife monitoring and tracking of different species. When it comes to small animals such as smaller birds, mammals, or even insects, the current approach is to use extremely lightweight RF tags to be located using radio telemetry. A new quantum leap in technology is needed to overcome these limitations and to enable new ways for observations of larger numbers of small animals. In an interdisciplinary team, we are working on the different aspects of such a new technology. In particular, we report on our findings on a sensor network based tracking solution for bats. Our system is based on integrated localization and wireless communication protocols for ultra-low power systems. This requires coding techniques for improved reliability as well as ranging solutions for tracking hunting bats. We address the technological and methodical problems related to system design, software support, and protocol design. First field experiments have been conducted that showcase the capabilities of our system.

The crucial first year: a longitudinal study of students’ motivational development at a Swiss Business School - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich (Higher Education)
In Switzerland, every student graduating from grammar school can begin to study at a university. This leads to high dropout rates. Although students’ motivation is considered a strong predictor of performance, the development of motivation during students’ transition from high school to university has rarely been investigated. Additionally, little is known about the relation of motivational aspects with other influences on study performance. The present longitudinal study addresses this research gap and examines the development of economics and management students’ study motivation. It encompasses four waves of data collected throughout the first year, using quantitative online surveys. In total, the sample consists of 820 students. Data is analysed using latent change modelling. Results indicate that students start at a higher level of intrinsic motivation compared to extrinsic motivation. The variability of the starting value of the two constructs is also differing. The analysis also shows a gradual decline in students’ motivation. Above all, the transition from secondary to higher education seems to be a driver for this decline.
Keywords: Transition to higher education; Motivation; Longitudinal study; Socio-cultural factors; Latent change model; Switzerland

Persönlichkeitsförderung im Schulunterricht, Band I: Realistische Ursachenzuschreibungen - Autorengruppe, Institut für Wirtschaftspädagogik
Jugendliche im Übergang von Schule zu Ausbildung befinden sich in einer Phase der Suche und Entwicklung ihrer eigenen Identität. Aus diesem Grund sollte die Schule nicht nur fachliche Kompetenzen vermitteln, sondern auch das Ziel einer Persönlichkeitsförderung der Schülerinnen und Schüler verfolgen. Das Unterrichtskonzept ermöglicht das Erlernen und Trainieren von wichtigen Selbst- und Sozialkompetenzen im Schulunterricht, damit die Lernenden schwierige Herausforderungen in verschiedenen Lebensbereichen besser bewältigen können. Das Unterrichtskonzept besteht aus verschiedenen Modulen, welche detailliert beschrieben sind und zahlreiche Übungen beinhalten. Die vorgeschlagene Verlaufsplanung kann individuell auf die jeweiligen Lernvoraussetzungen und Rahmenbedingungen des Unterrichts angepasst werden. Die Unterrichtsreihe «Persönlichkeitsförderung im Schulunterricht» wurde in Zusammenarbeit zwischen dem Institut für Wirtschaftspädagogik der Universität St. Gallen und vier Schulen des Kantons St. Gallen entwickelt und erprobt. Sie umfasst drei Bände: Band I «Realistische Ursachenzuschreibungen», Band II «Kommunikation in Konfliktsituationen» und Band III «Selbstwirksamkeit». Zielgruppe: Das Unterrichtskonzept dient als Arbeitsinstrument für Abschlussklassen Volksschule und Brückenangebote.

A typology of students’ enculturation during the first year at University - Jenert, Tobias; Brahm, Taiga; Gommers, Luci; Kühner, Patrizia
The first year of studying has been extensively researched in order to better understand the transition into Higher Education (HE) as well as the phenomena of student performance, retention, and drop out. Although research points to the importance of the socio-cultural dimension of first-year experiences, surprisingly little is known about the actual processes through which students integrate into the socio-cultural context of HE. To address this research gap, an interview study was conducted with 15 first-year university students. The analysis revealed distinctive transition processes into HE that were developed into a typology with four transition types. Interestingly, students who tended to be more critically reflective about their studies were in danger of having a rougher transition than less critically reflective counterparts. For the former, it is essential to develop social relationships that tie them to their studies while the latter manage study-related challenges by simply working through them.

Differentiating Novice, Non-expert and Expert Entrepreneurs: A Self-regulated Learning Perspective - Winkler, Christoph; Fust, Alexander; Jenert, Tobias (Academy of Management Proceedings)
Entrepreneurial contexts are characterized by uncertainty, often requiring entrepreneurs to adapt in order to tackle the corresponding challenges and succeed. While entrepreneurial success may be explained by experiential learning, little is known as to why some experienced entrepreneurs are more successful at adapting to uncertain conditions. It has been suggested that these differences are due to enhanced cognitive resources that are analogous to those of experts. Since expertise can be developed through self-regulated learning (SRL), our paper seeks to explain the missing link between experience and entrepreneurial success. By drawing from advances in expert research and a social cognitive view of self-regulation, we develop a process oriented model of self-regulated entrepreneurial learning (SREL) in order to explain why expert entrepreneurs are better able to self-regulate and adapt their behavior during uncertainty (compared to novices and non-experts). We further develop empirically testable research propositions, and discuss theoretical and practical implications for aspiring entrepreneurs and entrepreneurs alike.

Studienprogramm-Entwicklung in unterschiedlichen Spannungsfeldern - Dilger, Bernadette; Jenert, Tobias; Sloane, Peter F. E.

Von der Curriculum - zur Studienprogrammentwicklung: Argumente für eine Perspektiverweiterung - Jenert, Tobias (Pädagogische Hochschulentwicklung - Von der Programmatik zur Implementierung)

Mehr als nur „gute“ Stimmung: Einstellungen und Motivation Studierender als zentraler Bestandteil der Kompetenzentwicklung - Jenert, Tobias (Vortrag im Rahmen des Expert_Innenforums Hochschuldidaktik der Fachhochschule Oberösterreich.)

Loan Pricing: Do Borrowers Benefit from Cost-Efficient Banking? - Schlueter, Tobias; Busch, Ramona; Sievers, Soenke; Hartmann-Wendels, Thomas (Credit and Capital Markets--Kredit und Kapital)
This study examines the loan-pricing behavior of German banks for a large variety of retail and corporate loan products. We find that a bank’s operational efficiency is priced in bank loan rates and alters interest-setting behavior. Specifically, we establish that a higher degree of operational efficiency leads to lower loan markups, which makes prices more competitive and smoothes the setting of interest rates. By employing state-of-the-art stochastic frontier efficiency measures to capture a bank’s operational efficiency, we take a look at the bank customers’ perspective and demonstrate the extent to which bor-rowers benefit from cost-efficient banking.
Keywords: interest rate pass-through models; error correction models; bank efficiency; cost efficiency; stochastic frontier analysis

Utilizing big data analytics for information systems research: Challenges, promises and guidelines - Müller, Oliver; Junglas, Iris; vom Brocke, Jan; Debortoli, Stefan (European Journal of Information Systems)
Keywords: analytics; big data; data source; information systems research; methodology

The Role of Gender in Business Process Management Competence Supply - Gorbacheva, Elena; Stein, Armin; Schmiedel, Theresa; Müller, Oliver (Business and Information Systems Engineering)
Keywords: BPM workforce; Business process management; Competences; Gender diversity; Latent semantic analysis; Skills; Text mining

Text Mining for Information Systems Researchers: An Annotated Tutorial - Debortoli, Stefan; Müller, Oliver; Junglas, Iris; vom Brocke, Jan (Communications of the Association for Information Systems)
Keywords: Latent dirichlet allocation; Online customer reviews; Text mining; Topic modeling; User satisfaction